The Effect of Aqua and Resistance Trainings on Lipid Profile, Adiponectin, Insulin, and Glucose in Women with Gestational Diabetes Mellitus - Seyed Ali Hosseini; Nasibeh Kazemi; Reza Nouri; Mohammad Reza kordi; Maryam Kasraian (Mashhad University of Medical Sciences, 2018)
Introduction: Physical activity is one of basic solutions in the control and treatment of diabetes. Nevertheless, any kind of physical activity has different mechanisms in diabetic patients. Therefore, the aim of the present study was to compare the effect of aqua and resistance trainings on blood adiponectin, lipid profile, insulin, and glucose in patients with gestational diabetes mellitus (GDM). Methods: This randomized clinical trial was conducted in January, 2015 on 34 women with gestational diabetes referred to Motahari Clinic and Primatology Clinic of Hafez Hospital. The subjects were divided in three groups of aqua and resistance trainings and control. During 6 weeks, aqua and resistance training groups trained three 30-45-min sessions per week. The participants in the control group had just their daily activity. The levels of adiponectin, total cholesterol,high-density lipoprotein, triglyceride, fasting blood sugar, and insulin requirement were measured. The blood samples were collected in fasting status at the pre- and post-intervention phases. Data analysis was performed using t-test, analysis of covariance, one-way analysis of variance, and Bonferroni post-hoc test. P≤0.05 was considered statistically significant. Results: Aqua training had significant effect on increasing adiponectin and decreasing total cholesterol, triglyceride, and insulin requirement (P≤0.05). Resistance training had significant effect on the reduction of high-density lipoprotein, insulin requirement, and fasting blood sugar (P≤0.05). Additionally, aqua training rather had more effect on reduction of triglycerides in comparison to resistance training (P≤0.05). Conclusion: Aqua training had more positive effect on adiponectin and lipid profile in women with gestational diabetes in comparison to resistance training.